PENGARUH KOMPETENSI PROFESIONAL GURU TERHADAP PEMBELAJARAN IPS DI SMP NEGERI KOTA PALU - Taufiq Eka Riandhana (Center of Education Journal (CEJou), 2020)
The purpose of this study was to obtain information about the influence the professional competence of teachers for teaching social studies in SMP Palu. The method used is survey with descriptive quantitative data analysis techniques. The population in this study are all teachers IPS certified in Palu City Junior High School, as many as 116 people. Number of samples are 58 people using Proportional Stratified Random Sampling technique. Data collection techniques using Likert scale model questionnaires, interviews and documentation. Analysis of the data in this study using Normality Test Instruments, Test Analysis Coefficient of Determination, Validity Test Instruments, Test Reliability Test Instruments and Descriptive. Meanwhile, hypotheses using simple regression test. The results showed two-normally distributed variables to test for normality using the Kolmogorov-Smirnov Test and Analysis of reliability for variables X and Y calculated by Cronbach alpha formula. While on the significance test using the t test and F test at significance level with a value of α = 0.05. The results showed there is a positive and significant impact on the professional competence of learning with linear regression equation Y = 11.032 + 0,954X2 with a percentage of 29.2% significance.